RECONFIGURATION OF INTERFACE CHARGE STATES AND ITS EFFECT ON THE ELECTRO-PHYSICAL PROPERTIES OF METAL–DIELECTRIC–SEMICONDUCTOR STRUCTURES - Mamatkarimov, Odiljon Okhundedaevich; Abdulkhayev, Abrorbek Abdulloxonovich; Fazliddinov, Salokhiddin Bakhriddinovich; Quchqarov, Behzod Hoshimjonovich (SCIENCE and SOCIETY, 2026)
This work analyzes the physical mechanisms responsible for non-ideal electrical effects in metal–dielectric–semiconductor (MDS) structures. The study is based on the kinetic properties of charge states located at the interface and in the near-interface dielectric layer. It is shown that external influences modify the local potential landscape near the interface and redistribute charge-exchange kinetics without generating new defects. As a result, the electrical response of MDS structures is governed by the intrinsic kinetic dynamics of interface states.